CONDITIONS FOR THE USE OF CATALYSTS IN THE LIQUID PHASE - Safarov Meghli Djumayevich (Journals Park Publishing, 2022)
The purpose of this study is to develop methods for the synthesis of a number of pyrrol and its derivatives under normal conditions on the basis of commercially available raw materials in the presence of homogeneous catalysts.
Keywords: pyrrol; catalyst; chemical technology